2019
DOI: 10.1096/fj.201901715r
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin‐11 regulates the functions of caveolae and responds to mechanical stimuli in astrocytes

Abstract: Abbreviations: Cav, caveolin; EHD2, EH domain-containing protein 2; Flot-1, flotillin-1; LacCer, BODIPY FL C5-Lactosylceramide; Syt11, synaptotagmin-11; TfR, transferrin receptor. AbstractCaveolae play crucial roles in intracellular membrane trafficking and mechanosensation. In this study, we report that synaptotagmin-11 (Syt11), a synaptotagmin isoform associated with Parkinson's disease and schizophrenia, regulates both caveolaemediated endocytosis and the caveolar response to mechanical stimuli in astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…The bound proteins were eluted with elution buffer (in mM: 50 NaH 2 PO4, 300 NaCl, 50 imidazole, pH 8.0). The binding essay was performed according to Yan et al, (2020) with modifications. Briefly, purified GST-Syt11 and mutants (immobilized on Glutathione Sepharose TM 4B beads) were incubated with His-vti1a protein (2.5 μM) in 500 µl of reaction buffer (50 mM Tris-HCl, 100 mM NaCl, 0.5% Triton X-100, pH 8.0) at 4°C for 1 h. The bound fraction was washed five times with washing buffer (50 mM Tris-HCl, 150 mM NaCl, 0.5% Triton X-100, pH 8.0) and western blotting was performed.…”
Section: Purified Protein-binding Assays In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…The bound proteins were eluted with elution buffer (in mM: 50 NaH 2 PO4, 300 NaCl, 50 imidazole, pH 8.0). The binding essay was performed according to Yan et al, (2020) with modifications. Briefly, purified GST-Syt11 and mutants (immobilized on Glutathione Sepharose TM 4B beads) were incubated with His-vti1a protein (2.5 μM) in 500 µl of reaction buffer (50 mM Tris-HCl, 100 mM NaCl, 0.5% Triton X-100, pH 8.0) at 4°C for 1 h. The bound fraction was washed five times with washing buffer (50 mM Tris-HCl, 150 mM NaCl, 0.5% Triton X-100, pH 8.0) and western blotting was performed.…”
Section: Purified Protein-binding Assays In Vitromentioning
confidence: 99%
“…Therefore, different Syt family members play distinct roles in spontaneous release, most likely because of unique protein-protein and/or protein-lipid interactions. Syt11 plays multiple roles in membrane trafficking in neurons and glia (Bento et al, 2016;Du et al, 2017;Shimojo et al, 2019;Sreetama et al, 2016;Wang et al, 2016Wang et al, , 2018Yan et al, 2020). It regulates neuronal endocytosis, the autophagy-lysosome pathway, and synaptic plasticity; functions in lysosome exocytosis for membrane repair, caveolae-mediated endocytosis, and mechanoprotection in astrocytes; and inhibits phagocytosis and cytokine release in microglia.…”
Section: Introductionmentioning
confidence: 99%
“…Caveolae are 70-100 nm diameter sized plasma membrane invaginations that form bulb shape invaginations into the cytosol (Figure 1). They are found in a variety of cell types including adipocytes, endothelial cells, muscle cells, fibroblasts, and astrocytes (Cameron et al, 1997;Parton, 2003;Parton and Del Pozo, 2013;Parton et al, 2018;Yan et al, 2019). The plasma membranes of endothelial, muscle, and fat cells are packed with caveolae, suggesting an important role in specialized functions including homeostasis and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…GST pull‐down assays were described previously (Yan et al., 2020). Briefly, 5 mg of total proteins of brain extract were pre‐cleared by 20 μL of 50% glutathione sepharose beads for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported that Syt11 interacts with two PD‐causing genes— Parkin (Huynh et al., 2003; Wang et al., 2018) and ATP13A2 (Bento et al., 2016), and is a risk gene for PD (Nalls et al., 2011; Pihlstrom et al., 2013; Sesar et al., 2016). Syt11 is highly expressed in neurons and glia (Mittelsteadt et al., 2009) and plays diverse roles in the regulation of cytokine release and phagocytosis in macrophage and microglia (Du et al., 2017; Duque et al., 2013), membrane repair and caveolae functions in astrocytes (Sreetama et al., 2016; Yan et al., 2020), different modes of endocytosis, synaptic plasticity, and spontaneous neurotransmission in neurons (Li et al., 2021; Shimojo et al., 2019; Wang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%